Avaliação preliminar para implantação de um sistema de gerência de pavimentos em Tucuruí-PA – estudo de caso: bairro da Cohab - MIRANDA, Marcelo Chaves de (2018)
The prefectures in general, including in Tucuruí (PA), have faced increasing challenges in relation to the conservation of urban roads, requiring the development and application of modern systems of management and maintenance. A pavement management system (SGP) is able to coordinate a set of activities aimed at maintaining pavements in functional and structural conditions suitable to the needs of its users, providing a good infrastructure for economic and social development. This work aims to show, through literature review and field research, a preliminary experiment data collection about defects in floors in order to support the implementation of a GSP, subjective analysis, in order to analyze and detect defects in asphalt coatings in the floors of these roads, to then propose measures of maintenance and rehabilitation of pavements of streets and avenues of the neighborhoodThis pioneering work, as regards the assessment of the condition of the Tucuruí floors. The need for implementation of a new management system in maintenance, occurred in function of the evolution of cities as population issues and the number of vehicles that travel daily by their routes, as well as the need for safety, quality and low cost. 33-way were evaluated in field research, and on all roads in the neighborhood were found to be free of defects in floor coverings, and in all the streets, except the street of lilies, will require maintenance and rehabilitation activities. The most frequent defect was present in 29 material spill, which corresponds to 87.8% from total; the second most frequent defect was pot or hole in 27, which corresponds to 81.8% of total and the third most frequent defect was interconnected shrinkage crack or reflection on 21 routes, which corresponds to 63.6%. On the basis of data about defects in floors from field research and considering the proposed decision trees by Fernandes Jr. and Pantigoso (1998), the type of maintenance activity and more frequent rehabilitation will be patch which will be applied in 29, which corresponds to total 87.9%; the second most frequent activity will be drainage, which will be applied in developing the district 24 Cohab, which corresponds to the total and 72.7% the third most frequent activity will be sealant, which will be applied in 22 neighborhood routes Cohab, 66.7%. In general the routes Cohab feature large number of defects, reflecting a bad state of repair of flexible pavements, which generated a large amount of proposals for maintenance activities and rehabilitation of pavements which justifies the adoption of a more precise SGP in Tucuruí.